New lignans attenuating cognitive deterioration of Aβ transgenic flies discovered in Acorus tatarinowii. Issue 4 (15th February 2018) - Zhang, Wei-Yang; Feng, Xiao-Lin; Lu, Dan; Gao, Hao; Yu, Yang; Yao, Xin-Sheng
Graphical abstract: Highlights: Five new and three known lignans were isolated from Acorus tatarinowii . Stereochemistry of tatarinoid D was elucidated based on crystallographic data and CD. Tatarinoid D and the known compounds can improve cognitive defects of A β flies. Abstract: Five new lignan racemates, (±)-tatarinoid D–H (1 –5 ), and three known analogues (6 –8 ) were isolated from the rhizomes of Acorus tatarinowii . Their structures were established by 1D, 2D-NMR, HR-MS, IR and optical spectral data. Among them, 1 and6 –8 can alleviate the cognitive deterioration of A β transgenic flies.